PENGARUH MODEL NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI 1 SANGGEUE - Junaidah; Rifkina Zuhra (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2023)
This study aims to determine the effect of the Number Head Together model on the learning outcomes of fourth grade students at SD Negeri 1 Sanggeue. This type of research is experimental research with a pre-Experimental One Group Pretest-Posttest research design, namely giving tests before and after being given treatment. The sample of this research was 20 students of 4th grade SD Negeri 1 Sanggeue. Data collection techniques used were tests and interviews. The results of the research at SD Negeri 1 Sanggeu obtained the calculation of the t test where the significant value was 0.000 <0.05 with the tcount = 6.097 greater than ttable = 2.093, so that it can be said that Ha is accepted and Ho is rejected. Thus, it can be concluded that there is an effect of applying the Numbered Head Together model to improve student learning outcomes in class IV SD Negeri 1 Sanggeue.